The Influence of Gross Regional Domestic Income, Population Size, Inflation, and Investment on East Java Province's Local Income - Pramitha, Zetyra Dara; Asmara, Kiky (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the phenomenon of Local Income through the influence of Gross Regional Domestic Product, Population Size, Inflation, and Investment in the East Java Province. The data used in this study are secondary data from the years 2009 to 2022 sourced from the Central Statistics Agency of East Java Province. The research method employed is a quantitative method and processed using SPSS 25. The results of the analysis reveal that there is a significant simultaneous influence between the independent variables, namely Gross Regional Domestic Product (X1), Population Size (X2), Inflation (X3), Domestic Investment (X4), and Foreign Investment (X5), on the dependent variable, which is Local Income (Y), in the East Java Province. However, when examined individually, the Gross Regional Domestic Product variable has a positive and significant effect, Population Size has a negative and insignificant effect, inflation has a positive but insignificant effect, Domestic Investment variable has a positive but insignificant effect, and the Foreign Investment (FDI) variable has a negative and insignificant effect on Local Income in the East Java Province from 2009 to 2022.